2011
DOI: 10.1353/hpu.2011.0131
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Housing Instability, Food Insecurity, and Diabetes Self-Efficacy in Low-Income Adults

Abstract: Limited data exist on whether structural factors associated with poverty such as inadequate housing and food insecurity affect diabetes care. In a sample of low-income participants with diabetes (N=711), we sought to determine if housing instability was associated with lower diabetes self-efficacy, and whether this relationship was mediated by food insecurity. We ordered housing from most to least stable. We observed a linear decrease in diabetes self-efficacy as housing instability increased (p<.01). After ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 27 publications
3
76
0
Order By: Relevance
“…The determinants of food insecurity are multifactorial and complex, occur at multiple levels (the individual, social and environmental), and include poverty, social and economic disadvantage, individual characteristics and the political and social environments. Food insecurity can affect all stages of the lifespan (2)(3)(4)(5) , resulting in poor dietary intakes and negative health consequences (6)(7)(8)(9)(10)(11) . These outcomes place significant burden on health-care systems, thus food insecurity is a significant issue for individuals, households, communities and nations alike, yet there exists no internationally accepted measurement of individuals' and households' food security.…”
mentioning
confidence: 99%
“…The determinants of food insecurity are multifactorial and complex, occur at multiple levels (the individual, social and environmental), and include poverty, social and economic disadvantage, individual characteristics and the political and social environments. Food insecurity can affect all stages of the lifespan (2)(3)(4)(5) , resulting in poor dietary intakes and negative health consequences (6)(7)(8)(9)(10)(11) . These outcomes place significant burden on health-care systems, thus food insecurity is a significant issue for individuals, households, communities and nations alike, yet there exists no internationally accepted measurement of individuals' and households' food security.…”
mentioning
confidence: 99%
“…Among low-income urban households in these countries, food insecurity may be associated with unstable and vulnerable housing situations, such as living in shelters, in 'doubled up' or overcrowded housing scenarios, or in single-room occupancy (SRO) dwellings Food insecurity has been associated with homelessness in general samples of low-income households (12) as well as in studies of specific demographic groups, including families headed by single mothers (13) and street youth (14,15) . Other studies have found high rates of food insecurity among homeless or unstably housed individuals with co-occurring health or mental health conditions such as HIV/ AIDS, diabetes and psychiatric impairments (9,(16)(17)(18)(19)(20) . These studies have generally found that food insecurity is associated with worse health outcomes and greater drug and sex-related risk behaviours for people with these conditions.…”
mentioning
confidence: 99%
“…Piette et al [25] report that cost-related medication underuse is associated with higher hemoglobin A1c and worse self-reported functioning, while further studies of cost-related medication underuse also found worse diabetes control and increased complications [41,42]. Vijayaraghavan et al, in a study of 711 low-income adults with diabetes, found that housing instability [30] was associated with higher hemoglobin A1c levels.…”
Section: Overview Of Materials Need Insecurities In Diabetesmentioning
confidence: 99%
“…While a formally defined poverty level attempts to calculate the minimal income required to meet basic needs for an average person or household in a population, unmet material needs can still occur among individuals or households with incomes above poverty level if specific expenses exceed available resources. This can be of particular relevance to diabetes patients, who often have high out-of-pocket expenses for their care even with health insurance [19][20][21], and has led some to evaluate if material need insecurities are important for diabetes [22][23][24][25][26][27][28][29][30]. In addition, there has been increasing frustration with the failure to translate lifestyle interventions [31] that are efficacious in clinical trials into "real-world" settings.…”
Section: Introductionmentioning
confidence: 99%